Anisotropy of the thermoelectric figure of merit (ZT) in textured Ca3Co4O9 ceramics prepared by using a spark plasma sintering process - Lim, Chang-Hyun; Seo, Won-Seon; Lee, Soonil; Lim, Young Soo; Kim, Jong-Young; Park, Hyung-Ho; Choi, Soon-Mok; Lee, Kyu Hyoung; Park, Kyeongsoon (Journal of the Korean Physical Society, 2015)
Textured Ca 3 Co 4 O 9 ceramics were prepared by spark plasma sintering (SPS) from commercial CaCO 3 and Co 3 O 4 powders to investigate the thermoelectric anisotropy of Ca 3 Co 4 O 9 . The degree of orientation of the textured specimens was evaluated by using the Lotgering factor method, and the SPS process was confirmed to be an effective technology to prepare textured Ca 3 Co 4 O 9 ceramics. Both the power factors and the thermal conductivities were measured in two different directions, parallel (out-of-plane) and perpendicular (in-plane) to the SPS press axis. The difference in anisotropy between the electrical conductivity and the thermal conductivity was investigated for the textured Ca 3 Co 4 O 9 ceramics. The maximum figure of merit ( ZT ) value along the direction perpendicular to the SPS press axis was more than 20% higher than it was along the direction parallel to the SPS press axis. It is noted that the strong thermoelectric anisotropy can give rise to an overestimates of ZT when preparing samples in different directions for power factor and thermal conductivity measurements.